2020
DOI: 10.3389/fpls.2019.01763
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Microbial Ecology of Pasteuria and Nematode Species in Scottish Soils

Abstract: Pasteuria spp. are endospore forming bacteria which act as natural antagonists to many of the most economically significant plant parasitic nematodes (PPNs). Highly speciesspecific nematode suppression may be observed in soils containing a sufficiently high density of Pasteuria spp. spores. This suppression is enacted by the bacteria via inhibition of root invasion and sterilization of the nematode host. Molecular methods for the detection of Pasteuria spp. from environmental DNA (eDNA) have been described; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…and the Grampositive endospore forming bacterial micro-parasite Pasteuria ramosa Metchnikoff has become a valuable model for studying co-evolutionary relationships where it is reported that the binding of endospores, a key stage in the infection process, is genetic and under negative frequency-dependent selection (also known as "Red Queen dynamics") and not linked to environmental factors (Decaestecker et al, 2007;Ebert et al, 2016). However, meta-barcoding studies in Scottish soils suggest that Pasteuria communities are structured and correlate with environmental factors including soil carbon, moisture and pH (Orr et al, 2020) suggesting and environmental component to this nematode hyperparasite interaction.…”
Section: Introductionmentioning
confidence: 99%
“…and the Grampositive endospore forming bacterial micro-parasite Pasteuria ramosa Metchnikoff has become a valuable model for studying co-evolutionary relationships where it is reported that the binding of endospores, a key stage in the infection process, is genetic and under negative frequency-dependent selection (also known as "Red Queen dynamics") and not linked to environmental factors (Decaestecker et al, 2007;Ebert et al, 2016). However, meta-barcoding studies in Scottish soils suggest that Pasteuria communities are structured and correlate with environmental factors including soil carbon, moisture and pH (Orr et al, 2020) suggesting and environmental component to this nematode hyperparasite interaction.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Vink et al (2014) assessed the temporal and land use effects on soil bacterial community structure from a range of Machair habitats throughout the Outer Hebrides archipelago. Orr et al (2020) included Machair soil in their study of Pasteuria, endospore forming bacteria that are considered natural antagonists to soilborne nematodes.…”
Section: Introductionmentioning
confidence: 99%